Financial Development and Foreign Direct Investment Impact on Economic Growth: Evidence from Nepal - Pandey, Abhishek; Shrestha, Zenisha; Acharya, Krishna Raj (Journal of Innovation in Academia, 2024)
The interplay among financial development, foreign direct investment (FDI), and economic growth has been a subject of keen interest among scholars, both from a theoretical standpoint and through empirical research. Focusing on Nepal, this study examines the distinctive connections among economic expansion, the influx of foreign capital, and the evolution of the financial sector. Given the lack of a definitive metric for financial development, this research adopts the financial development index, along with the financial institution index and financial market index, as alternative indicators. It also considers additional variables that could influence economic growth beyond financial development and FDI. Utilizing the Autoregressive Distributed Lag (ARDL) bounds testing method and the Error Correction Model (ECM), the analysis uncovers a robust positive link between financial development and FDI in enhancing Nepal's economic output. Furthermore, both the short-term and long-term analyses prove to be reliable, devoid of issues like heteroscedasticity, autocorrelation, and multicollinearity. Importantly, the findings indicate that in the face of short-term disruptions, the dynamics between these variables adjust back to a long-term equilibrium state.